SURVEY FHYSICAL FITNESS BOLA BASKET PUTRA EKSTRAKURIKULER SMA AL-AZHAR SYIFA BUDI PEKANBARU - OKI CANDRA; Wahyudi Wahyudi (Jurnal Muara Olahraga, 2019)
This study aims to determine how the level of physical fitness in basketball extracurricular students at Al-Azhar Syifa Budi Pekanbaru High School students. The population and sample in this study were 14 people while the sampling technique in this study was total sampling. From the results of tests conducted in the field there were 3 people or 21.42% classified as good condition level, 3 people or 21.42% were classified as moderate, 7 people or 50% were classified as less, and 1 person or 7.14 were classified as very poor. Based on the results of research and analysis of data that has been revealed, the physical fitness score was obtained 14.21 in the percentage of 21.42% so that it can be concluded that physical fitness in extracurricular students of Al-Azhar men's basketball Syifa Budi Pekanbaru is in the Medium category.